Exploration of non-pharmacological interventions in Behavioral and Psychological Symptoms of Dementia (BPSD) / Nur Sabiha Md Hussin. - Md Hussin, Nur Sabiha (2019)
Dementia is a global epidemic and the incidence is in a growing trend. Behavioral and Psychological Symptoms in Dementia (BPSD) is an integral element of dementia which appears in any stage of dementing. these symptoms do not only impair the well-being, activities of daily life and quality of life of people with dementia but they also cause immense burden to the care providers.